Leadership on stage - Marques, Margarida de Bessa Ferreira Rodrigues (2018)
In dynamic and fast-changing markets leaders are required that go beyond transactional logics, being able to be creative, to improvise, and articulate dynamic capabilities. This description goes more in line with the profile of a choreographer than that of a chief executive. This study is intended to test whether transformational leadership is backed up by individuals’ RIASEC profile of a choreographer (Artistic, Social, and Enterprising) in comparison to that of a chief executive (conventional and enterprising). Hence, it intends to test the value of implementing arts-based methods in analytics-based courses. With a sample comprising 117 participants, we tested differences in leadership style against respondents’ academic background (59 individuals with creativity-based education and 58 respondents of analytical-based education) as well as RIASEC predictors of transformational leadership in each group. Results show no significant differences in the style of leadership associated with respondents’ academic background. Nevertheless, the hypothesis that defines a positive association between the choreographer profile and the transformational leadership, in the sample group of the analytical-based individuals, is corroborated.